2020
DOI: 10.1007/978-3-030-59426-8
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of Recognition and Multicultural Policies in Colombia and New Zealand

Abstract: This dissertation discusses recognition as a theoretical concept and a political practice. The thesis argues that currently, theories of recognition are conflated with theories of liberal multiculturalism, according to which recognition emerges through political practices that emphasise group-differentiated rights in plural societies. The thesis argues that in many cases, however, these political practices fail to realise the normative ideals of recognition theory. The argument is supported by an analysis of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In fact, there is an ample amount of lesson-drawing scholarship that helps countries to design their policies. Among this scholarship between industrialized and developing nations Pirsoul (2018) studies the multicultural policy in New Zealand and Colombia. He concluded that there is a gap in both nations related to general population and elites understand multicultural policies that have been not successful.…”
Section: The Lesson-drawing Approachmentioning
confidence: 99%
“…In fact, there is an ample amount of lesson-drawing scholarship that helps countries to design their policies. Among this scholarship between industrialized and developing nations Pirsoul (2018) studies the multicultural policy in New Zealand and Colombia. He concluded that there is a gap in both nations related to general population and elites understand multicultural policies that have been not successful.…”
Section: The Lesson-drawing Approachmentioning
confidence: 99%